Data Supporting 'Efficacy of bioadmendments in reducing the influence of salinity on the bioremediation of oil-contaminated soil' - Atai, Emmanuel; Pawlett, Mark; Coulon, Frederic (Cranfield University, 2023)
Data to support the paper: 'Efficacy of bioadmendments in reducing the influence of salinity on the bioremediation of oil-contaminated soil', which include hydrocarbon alkanes and PAHs, PLFA Mol% to give the microbial community dynamics and abundance of the groups, basal and multisubstrate respiration, and the correlation of the entire datasets. Some statistics and Charts were included in the data.
Keywords: Biochar'; 'spent mushroom compost'; 'bioamendment'; 'hydrocarbon'; 'microbial community'